Pharmaceutical Prescribing Patterns and Costs During Hurricane Harvey Shelter Operations in Dallas, Texas. Issue Volume 34:Issue s1(2019) (May 2019) - Liu, E. Liang; Joseph, Alysha; Flax, Lindsay A.; Fowler, Raymond L.; Klein, Kelly R.; Swienton, Raymond E.
Abstract : Introduction: Hurricane Harvey made landfall in southeast Texas in August 2017, causing unprecedented flooding throughout the Texas coastal region. Residents of affected regions were forced to evacuate to nearby unaffected areas, including Dallas, TX, where a large shelter operation was opened for 23 days to care for those evacuees. Retrospective evaluation of pharmaceutical prescribing patterns for the evacuees who self-presented to the Megashelter Medical Clinic (MMC) established in the shelter contributes to developing evidence-based planning strategies for healthcare delivery in the post-disaster setting. Aim: To describe the pharmacy needs of a displaced population following a large-scale evacuation after a hurricane Methods: De-identified prescription records written and filled at a shelter pharmacy were reviewed, looking at both cost and category of medications dispensed over time. Results: Approximately 41% of evacuees with a total of 2, 654 visits utilized the MMC clinic, resulting in 1, 590 prescriptions filled with an associated cost of 78, 039. The most commonly prescribed drug categories were cardiovascular (21.2%), neuropsychotropic (15.6%), infectious disease (12.5%), and endocrine (9.6%). While the most commonly dispensed were antihypertensives, diabetes treatment-related prescriptions, antibacterials, antidepressants, and NSAIDs, the costliest individual prescriptions were antiretrovirals and antipsychotics. Discussion: Prescribing patterns for the MMC differed from normal prescribing patterns of a general population. Of the prescriptions dispensed at the MMC, pharmaceutical prescription patterns suggest the immediate needs of evacuees differ from later needs. There is a greater need for chronic disease management in the early phase of shelter operations, and an increasing need for neuropsychotropic and infectious disease prescriptions over time. Understanding overall patterns of drug utilization over the duration of the shelter provides valuable insight on post-disaster medical resource utilization in evacuee populations.